Curriculum Policy and Educational Quality Enhancement: Examining the Role of the Merdeka Curriculum in Achieving Excellence Accreditation - Untung Khoiruddin; AB. Musyafa Fathoni (Al-Qalam Institue, 2025)
The implementation of the Merdeka Curriculum has become a strategic policy for improving educational quality and supporting higher education institutions in achieving Excellence Accreditation. However, empirical evidence explaining how curriculum policy contributes to institutional transformation and quality enhancement remains limited. This study examines the role of the Merdeka Curriculum in enhancing educational quality and supporting Excellence Accreditation in the Islamic Education Management Study Programs at university. A qualitative multiple-case study was employed using semi-structured interviews, participant observations, document analysis, and field notes. Data were analyzed through the interactive model of Miles, Huberman, and Saldaña, comprising data condensation, data display, and conclusion drawing. The findings reveal three major themes: curriculum institutionalization as a strategic governance framework, experiential learning and institutional collaboration as drivers of implementation, and adaptive governance with continuous quality improvement in addressing organizational challenges. The study concludes that effective curriculum implementation requires integrating curriculum reform with governance and quality assurance. It contributes an institutional framework linking curriculum policy, organizational transformation, and excellence accreditation.